2006
DOI: 10.1038/modpathol.3800532
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the CDK inhibitor p27kip1 and oxidative DNA damage in non-neoplastic and neoplastic vulvar epithelial lesions

Abstract: Vulvar cancer represents an important medical problem worldwide whose incidence is increasing at an alarming rate in young females. Several factors have been linked to vulvar cancer development, but its exact pathogenesis remains to be determined. Vulvar tumorigenesis proceeds through intermediate dysplastic lesions, known as vulvar intraepithelial neoplasias, frequently associated with non-neoplastic epithelial disorders of the vulva, such as lichen sclerosus and squamous cell hyperplasia. In this study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In contrast subsequent investigations revealed that some cases of squamous hyperplasia were found not only be monoclonal but also to show increased expression of p53 and allelic imbalance [17–20]. In another recent study, it was demonstrated that expression of p27 (Kipl) was down‐regulated while oxidative DNA damage increased from non‐neoplastic epithelial disorder through vulvar epithelial neoplasia to invasive vulvar carcinoma [21]. These findings may support the hypothesis that there may be a pathway of neoplastic transformation from SH to invasive carcinoma.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast subsequent investigations revealed that some cases of squamous hyperplasia were found not only be monoclonal but also to show increased expression of p53 and allelic imbalance [17–20]. In another recent study, it was demonstrated that expression of p27 (Kipl) was down‐regulated while oxidative DNA damage increased from non‐neoplastic epithelial disorder through vulvar epithelial neoplasia to invasive vulvar carcinoma [21]. These findings may support the hypothesis that there may be a pathway of neoplastic transformation from SH to invasive carcinoma.…”
Section: Discussionmentioning
confidence: 95%
“…These data strongly suggest that aging‐associated oxidative DNA damage could favor the initial steps of cancer initiation. In support of this initiator role, multiple studies have shown the presence of oxidative DNA damage in early lesions at levels lower, 59,87 similar, 88 or even greater 89 than levels in high‐grade progressing tumors. However, it is clear that the high level of oxidative stress maintained in cancer cells should also contribute to cancer progression.…”
Section: Senescence‐associated Oxidative Damage Is Mutagenic and Possmentioning
confidence: 94%
“…Immunohistochemical analyses were performed on routinely processed, formalin-fixed, paraffin-embedded tissues employing an avidin–biotin complex immunoperoxidase technique, as previously described [12,13]. A specific polyclonal anti-CD133 antibody (Santa Cruz Biotechnology, Santa Cruz, CA, USA; 1:100) was used for the staining.…”
Section: Methodsmentioning
confidence: 99%